(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2021)
Socio-economic development of mountainous rural areas is one of the important problems of our republic. Mountainous areas are cattle-breeding areas. They are characterized by natural, man-made values, favorable climatic conditions and crafts, resources, the proper use of which can be a stimulus not only for the stabilization of mountain settlements, but also for their development. Mountainous areas are favorable areas for the organization of various forms of tourism. In the article, based on the generalization of the factual material, the current problems of the main features of the mountainous rural settlements of the Republic of Armenia are presented: settlement, specialization, infrastructure.